Impact of iatrogenic biliary injury during laparoscopic cholecystectomy on surgeon's mental distress: a nationwide survey from China. Issue 12 (December 2020) - Dai, Hai-Su; Liang, Lei; Zhang, Cheng-Cheng; Cheng, Zhang-Jun; Peng, Yong-Hai; Zhang, Yao-Ming; Geng, Xiao-Ping; Qin, Hong-Jun; Wang, Kai; Chen, Wei; Yu, Chao; Wang, Li-Fei; et al.
Abstract: Background: Iatrogenic biliary injury (IBI) following laparoscopic cholecystectomy (LC) is the most serious iatrogenic complications. Little is known whether LC-IBI would lead to surgeon's severe mental distress (SMD). Methods: A cross-sectional survey in the form of electronic questionnaire was conducted among Chinese general surgeons who have caused LC-IBI. The six collected clinical features relating to mental distress included: 1) feeling burnout, anxiety, or depression, 2) avoiding performing LC, 3) having physical reactions when recalling the incidence, 4) having the urge to quit surgery, 5) taking psychiatric medications, and 6) seeking professional psychological counseling. Univariable and multivariable analyses were performed to identify risk factors of SMD, which was defined as meeting ≥3 of the above-mentioned clinical features. Results: Among 1466 surveyed surgeons, 1236 (84.3%) experienced mental distress following LC-IBI, and nearly half (49.7%, 614/1236) had SMD. Multivariable analyses demonstrated that surgeons from non-university affiliated hospitals (OR:1.873), patients who required multiple repair operations (OR:4.075), patients who required hepaticojejunostomy/partial hepatectomy (OR:1.859), existing lawsuit litigation (OR:10.491), existing violent doctor–patient conflicts (OR:4.995), needing surgeons' personal compensation (OR:2.531), and additional administrative punishment by hospitals (OR:2.324) were independent risk factors of surgeon's SMD. Conclusion: Four out of five surgeons experienced mental distress following LC-IBI, and nearly half had SMD. Several independent risk factors of SMD were identified, which could help to make strategies to improve surgeons' mental well-being.